"The island of living hope" leprosy erdaication publicity in the late American colonial Philippines - Acosta, Joshua Gabriel (Philippine Studies: Historical and Ethnographic Viewpoints, 2025)
This article examines leprosy eradication discourses in the American colonial Philippines. It argues that narratives about leprosy treatment became a site for negotiating political claims over medical authority during heightened nationalist sentiment in the 1920s and 1930s. As Filipino physicians levied critiques of colonial public health efforts in addressing leprosy care, American colonial and humanitarian officials enlisted Filipino leprosy patient-inmates and physician collaborators as affective ambassadors to recapitulate a benevolent rendering of colonial medical interventions. These dynamics underscore how the framing of leprosy care was jointly constituted with the shifting political landscape during the latter decades of US rule.